Activities of two dissimilar thioredoxins from the cyanobacterium Anabaena sp. strain PCC 7120. - Gleason, F K (1992)
Thioredoxin is a small redox protein that functions as a reducing agent and modulator of enzyme activity. A gene for an unusual thioredoxin was previously isolated from the cyanobacterium Anabaena sp. strain PCC 7120 and cloned and expressed in Escherichia coli. However, the protein could not be detected in Anabaena cells (J. Alam, S. Curtis, F. K. Gleason, M. Gerami-Nejad, and J. A. Fuchs, J. Bacteriol. 171:162-171, 1989). Polyclonal antibodies to the atypical thioredoxin were prepared, and the protein was detected by Western immunoblotting. It occurs at very low levels in extracts of Anabaena sp. and other cyanobacteria. No antibody cross-reaction was observed in extracts of eukaryotic algae, plants, or eubacteria. The anti-Anabaena thioredoxin antibodies did react with another unusual thioredoxin-glutaredoxin produced by bacteriophage T4. Like the T4 protein and other glutaredoxins, the unusual cyanobacterial thioredoxin can be reduced by glutathione. The Anabaena protein can also activate enzymes of carbon metabolism and has some functional similarity to spinach chloroplast thioredoxin f. However, it shows only 23% amino acid sequence identity to the spinach chloroplast protein and appears to be distantly related to other thioredoxins. The data indicate that cyanobacteria, like plant chloroplasts, have two dissimilar thioredoxins. One is related to the more common protein found in other prokaryotes, and the other is an unusual thioredoxin that can be reduced by glutathione and may function in glucose catabolism.